DEATH AND THE MODERN EMPIRE: THE 1918–19 INFLUENZA EPIDEMIC IN INDIA. (December 2019) - Arnold, David
ABSTRACT: In India the 1918–19 influenza pandemic cost at least twelve million lives, more than in any other country; it caused widespread suffering and disrupted the economy and infrastructure. Yet, despite this, and in contrast to the growing literature on recovering the 'forgotten' pandemic in other countries, remarkably little was recorded about the epidemic in India at the time or has appeared in the subsequent historiography. An absence of visual evidence is indicative of a more general paucity of contemporary material and first-hand testimony. In seeking to explain this absence, it is argued that, while India was exposed to influenza as a global event and to the effects of its involvement in the Great War, the influenza episode needs to be more fully understood in terms of local conditions. The impact of the disease was overshadowed by the prior encounter with bubonic plague, by military recruitment and the war, and by food shortages and price rises that pushed India to the brink of famine. Subsumed within a dominant narrative of political unrest and economic discontent, the epidemic found scant expression in official documentation, public debate and/or even private correspondence.